Evaluation of the School Literacy Movement in Primary Schools - Meri Meri; Sofyan Sofyan; Yanto Yanto (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research aims to evaluate the implementation of a literacy program based on predetermined indicators, with the expectation that the findings will benefit future policy formulation. The research used a qualitative approach, specifically the Context, Input, Process, and Product (CIPP) evaluation. Data collection involved interviews and observations. The School Literacy Movement is a government initiative aimed at improving literacy levels in Indonesia. In the Muaro Jambi District, a primary school serving as an implementer of the School Literacy Movement experienced a decline in literacy education based on educational report card scores. After conducting the research, it was found that the school already had clear goals in the context, but it required additional inputs such as integrating the vision and mission to motivate teachers and students, establishing a School Literacy Team (TLS), implementing Standard Operating Procedures (SOP), and optimizing the use of facilities and resources. In the process, academic supervision and creativity in finding appropriate learning media were still needed, along with personalized guidance for students to identify their learning styles to ensure that the outcomes aligned with the intended goals. The research highlights the importance of various factors in implementing the literacy program, and the findings can contribute to improving future literacy policies in schools.